SiO2 / PAA-b-PFADE amphiphilic Janus nanosphere as well as preparation method and application thereof
Through the preparation and application of SiO2/PAA-b-PFADE amphiphilic Janus nanospheres, the problem of stability and vulnerability of ultra-double-spark materials under extreme conditions is solved, and the ultra-double-spark with high wear resistance and durability is achieved. Coating, suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411744012.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-30
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-30
AI Technical Summary
The existing ultra-double sparse materials have poor stability under extreme climatic conditions and are vulnerable to micro-nano structures, resulting in reduced coating performance and shortened service life.
Using SiO2/PAA-b-PFADE amphiphilic Janus nanospheres, the acylation reaction of SiO2 nanospheres modified with γ-aminopropyltriethoxy silicon and amphiphilic fluorine-containing block copolymer PAA-b-PFADE , nanospheres with palsy characteristics were prepared, and a super double-spray coating was constructed through the nanospheres. The low surface energy provided by its micro-nano rough structure and organic liquid-spray chain segments were used to improve the wear resistance and durability of the coating. .
It significantly improves the wear resistance and durability of the ultra-double coating, maintains good waterproof, oilproof and stain resistance, and maintains high-efficiency performance for a long time even under extreme conditions.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional coating development, and relates to SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres and a preparation method and application thereof. Background Art
[0002] In recent years, as a cutting-edge scientific and technological innovation, super-amphiphobic surface technology is gradually showing its great application potential in many fields. This surface technology has shown remarkable effects in self-cleaning, surface corrosion protection, anti-icing and other aspects due to its unique waterproof and oil-proof properties. It not only has a wide range of application prospects in daily life, such as realizing self-cleaning functions in clothing, furniture, building exterior walls and other fields, reducing the cost of manual maintenance; in the biomedical field, super-amphiphobic surface technology also shows great potential, such as anti-fouling treatment of medical devices, improving the cleanliness and safety of surgical instruments; in addition, in the military field, this technology can be used for the surface treatment of aircraft, ships and other equipment, effectively reducing corrosion and icing problems in marine environments or severe weather conditions, and improving the combat effectiveness and durability of equipment.
[0003] However, despite the broad prospects of super-amphiphobic surface technology, existing super-amphiphobic materials still face a series of challenges in practical applications. Among them, the stability problem of low surface energy materials is particularly prominent. Such materials are often easily affected by environmental factors such as temperature, light, and strong oxidants, resulting in decomposition of the material structure or degradation of performance. Especially under extreme climatic conditions, such as high temperature and strong ultraviolet radiation, the stability problem of low surface energy materials is more prominent, which undoubtedly limits the widespread application of super-amphiphobic surface technology.
[0004] In addition, the fragility of micro-nano structures is also a major problem facing current super-amphiphobic materials. Micro-nano structures are the key to achieving water and oil repellency on super-amphiphobic surfaces, but these delicate structures are easily damaged by mechanical friction or wear. Once the micro-nano structures are damaged, the adhesion and super-amphiphobic properties of the coating will be greatly reduced or even completely lost, which will seriously affect the service life and application effect of the super-amphiphobic surface. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a SiO2 / PAA-b-PFADE amphiphilic Janus nanosphere and a preparation method and application thereof, thereby solving the technical problem of poor durability of superamphiphobic materials in the prior art.
[0006] The present invention is achieved through the following technical solutions: A method for preparing SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres comprises the following steps: SiO2 nanospheres and hexadecyltrimethylammonium bromide are added into a two-phase solvent of water and toluene, and then the pH value of the system is adjusted to 7-8, and γ-aminopropyltriethoxysilane is added for reaction to obtain γ-aminopropyltriethoxysilane-modified SiO2 nanospheres; Acrylic acid, 4-cyano-4-(phenylthioformylthio) valeric acid and azobisisobutyronitrile are added to tetrahydrofuran for a primary reaction to obtain a first product; the first product, perfluorodecyl acrylate and azobisisobutyronitrile are added to tetrahydrofuran for a secondary reaction to obtain an amphiphilic fluorinated block copolymer PAA-b-PFADE; The amphiphilic fluorinated block copolymer PAA-b-PFADE, a catalyst and ethanol are mixed, ultrasonically dispersed, and the γ-aminopropyltriethoxysilane-modified SiO2 nanospheres are added. After reaction, the SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres are obtained.
[0007] Preferably, the particle size of the SiO2 nanospheres is 30-500 nm.
[0008] Preferably, the ratio of the SiO2 nanospheres to γ-aminopropyltriethoxysilane is (0.5-3.0) g: (100-600) μL.
[0009] Preferably, the mass ratio of acrylic acid to 4-cyano-4-(phenylthiocarbothioylthio)pentanoic acid and perfluorodecyl acrylate is 7:0.2:(15.5-51.8).
[0010] Preferably, during the primary reaction, the reaction temperature is 75-90° C. and the reaction time is 7-12 h; during the secondary reaction, the reaction temperature is 75-90° C. and the reaction time is 7-12 h.
[0011] Preferably, the mass ratio of the amphiphilic fluorinated block copolymer PAA-b-PFADE to the γ-aminopropyltriethoxysilane-modified SiO2 nanospheres is (0.03-0.18):(0.075-0.45).
[0012] A SiO2 / PAA-b-PFADE amphiphilic Janus nanosphere is prepared by the above method.
[0013] The above-mentioned SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres are used in the preparation of super-amphiphobic coatings. First, a hydroxyl acrylic resin prepolymer solution is coated on the surface of the substrate, and then a mixed solution of a cross-linking agent and the SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres is coated, and a super-amphiphobic coating is obtained after drying.
[0014] Preferably, the coating amount of the hydroxy acrylic resin prepolymer solution, the crosslinking agent and the SiO2 / PAA-b-PFADE amphiphilic Janus nanosphere mixed solution is 0.05-0.06 mL / cm 2 The concentration of the hydroxy acrylic resin prepolymer solution is 0.1-0.6 g / mL, and the concentration of SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres in the mixed solution of the crosslinking agent and SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres is 0.01-0.035 g / mL.
[0015] A super amphiphobic coating is prepared by the above method; the super amphiphobic coating has an oil contact angle of 150°~157°, an oil rolling angle of 2.6°~9.4°, a water contact angle of 152°~160°, and a water rolling angle of 1.9°~9°.
[0016] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a method for preparing SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres. At a water-organic two-phase interface, hydrophilic amino groups are grafted onto a portion of the surface of the SiO2 nanospheres, and the original hydroxyl groups are retained on a portion, and an amphiphilic fluorinated block copolymer is further grafted onto the amino groups to provide superphobic segments and prepare an amphiphilic coating. In the preparation process, in the presence of 4-cyano-4-(phenylthioformylthio)pentanoic acid, acrylic acid and perfluorodecyl acrylate are respectively used as hydrophilic and hydrophobic monomers, and a RAFT polymerization method is used to obtain a hydrophilic and hydrophobic coating. An amphiphilic fluorinated block copolymer was prepared to obtain an amphiphilic fluorinated block copolymer PAA-b-PFADE. The reactive group carboxyl of the hydrophilic chain segment was used to react with the reactive group amino group at one end of the NH2-SiO2 nanosphere modified by γ-aminopropyltriethoxysilane in an ethanol solution to obtain SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres. Through this process, the surface of the SiO2 nanospheres was partially hydrophilic and partially hydrophobic, thus realizing the construction of amphiphilic nanoparticles. When the amphiphilic nanoparticles were used to construct a coating, the inorganic end was oriented toward the hydroxyl acrylate coating, and the organic lyophobic chain segment was oriented toward the air. The micro-nano rough structure constructed by the SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres and the low surface energy material provided by the organic lyophobic chain segment were used to realize the super-amphiphobic performance of the coating. In addition, the reactive group hydroxyl of the inorganic end was chemically cross-linked with the cross-linking agent to improve the wear resistance of the coating, thereby effectively improving the durability of the coating.
[0017] Furthermore, the particle size of the SiO2 nanospheres is 30~500nm. By regulating the particle size of the nanospheres, different micro-nano dual-scale rough structures can be formed, thereby giving the coating differentiated super-amphiphobic properties, including changes in water contact angle, oil contact angle and rolling angle, to adapt to the specific requirements of super-amphiphobic properties in different application scenarios.
[0018] Furthermore, the ratio of the SiO2 nanospheres to γ-aminopropyltriethoxysilane is (0.5~3.0) g:(100~600) μL. By adjusting the ratio of the two, the grafting rate of γ-aminopropyltriethoxysilane on the surface of the SiO2 nanospheres can be controlled, thereby affecting the number and distribution of reactive groups on the surface of the SiO2 nanospheres, providing a regulatory basis for subsequent functional modification.
[0019] Furthermore, the mass ratio of acrylic acid to 4-cyano-4-(phenylthioformylthio)pentanoic acid and perfluorodecyl acrylate is 7:0.2:(15.5-51.8). By adjusting the ratio of the three, the length of the fluorinated monomer chain segment at the hydrophobic end of the fluorinated block copolymer can be accurately controlled, thereby obtaining a fluorinated block copolymer with excellent performance. The copolymer can significantly improve the super-amphiphobic properties of the coating, including higher water contact angle and oil contact angle, and lower rolling angle.
[0020] Furthermore, in the primary reaction process, the reaction temperature is 75-90°C and the reaction time is 7-12h; in the secondary reaction process, the reaction temperature is 75-90°C and the reaction time is 7-12h. By controlling the reaction temperature and reaction time, the hydrolysis environment of γ-aminopropyltriethoxysilane can be adjusted, thereby affecting its grafting rate on the surface of SiO2 nanospheres. The change in grafting rate further regulates the number and distribution of reactive groups on the surface of SiO2 nanospheres, providing scientific basis and technical support for subsequent functional modification.
[0021] Furthermore, the mass ratio of the amphiphilic fluorinated block copolymer PAA-b-PFADE to the γ-aminopropyltriethoxysilicon modified SiO2 nanospheres is (0.03~0.18):(0.075~0.45). By regulating this mass ratio, the performance of the obtained SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres is optimized, and the super-amphiphobic properties of the coating are improved, including higher water contact angles and oil contact angles, and lower rolling angles, thereby enhancing the waterproof, oil-proof and anti-fouling capabilities of the coating.
[0022] Furthermore, the present invention also discloses an application of SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres in the preparation of a super-amphiphobic coating, wherein a hydroxylated acrylic resin prepolymer solution is first coated on the surface of the substrate, and then a crosslinking agent and the SiO2 / PAA-b-PFADE amphiphilic Janus nanosphere mixed solution are coated, and the super-amphiphobic coating is obtained after drying. The coating amount of the hydroxylated acrylic resin prepolymer solution and the crosslinking agent and the SiO2 / PAA-b-PFADE amphiphilic Janus nanosphere mixed solution is 0.05-0.06 mL / cm 2 The concentration of the hydroxy acrylic resin prepolymer solution is 0.1-0.6 g / mL, and the concentration of SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres in the mixed solution of the crosslinking agent and SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres is 0.01-0.035 g / mL. The optimized design of the above parameters can enhance the crosslinking effect of SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres in the coating, thereby giving the super amphiphobic coating excellent durability, including higher wear resistance and long-term waterproof and oil-proof properties.
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 Transmission electron microscope image of silver-labeled NH2-SiO2Janus nanospheres; Figure 2 Transmission electron microscopy image of SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres Figure 3 This is a photo of SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres stabilized emulsion; Figure 4 Contact angle test results of different liquids on the super-amphiphobic coating prepared in Example 2 of the present invention after thirty friction tests; Figure 5 The water contact angle and rolling contact angle test results of the super-amphiphobic coating constructed based on SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres prepared in Example 2 of the present invention after different cyclic friction tests; Figure 6The test results of hexadecane contact angle and rolling contact angle of the super amphiphobic coating constructed based on SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres prepared in Example 2 of the present invention after different cyclic friction tests. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0026] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0027] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0028] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0029] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0030] The present invention provides a method for preparing SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres, comprising the following steps: S1: Add SiO2 nanospheres and hexadecyltrimethylammonium bromide to a two-phase solvent of water and toluene, stir at 20-40°C for 20-40 minutes, so that the SiO2 nanospheres are stably dispersed at the interface of the two phases of water and toluene, then add ammonia water to adjust the pH value of the system to 7-8, and stir the system at a temperature of 85-95°C for 1-6 hours to stabilize the system, finally add γ-aminopropyltriethoxysilane, react at 85-95°C for 1-6 hours, and obtain γ-aminopropyltriethoxysilane-modified SiO2 nanospheres; Specifically: The particle size of SiO2 nanospheres is 30~500nm, and they are solid nanospheres.
[0031] The preparation method of the SiO2 nanospheres is as follows: 10 mL of ammonia water, 50-250 mL of anhydrous ethanol and 30 mL of deionized water are added to a three-necked flask equipped with a digital display stirrer, and after stirring evenly at 30°C for 20 minutes, 10 mL of ethyl orthosilicate is added, and the reaction is continued for 5 hours. After the reaction is completed, SiO2 nanospheres with a particle size of 30-500 nm are obtained through centrifugation, washing and drying steps.
[0032] The ratio of SiO2 nanospheres to γ-aminopropyltriethoxysilane is (0.5~3.0) g: (100~600) μL; The ratio of SiO2 nanospheres to dispersant water and toluene is (0.5~3.0) g: (50~300) mL: (10~60) mL; The mass ratio of SiO2 nanospheres to hexadecyltrimethylammonium bromide is (0.5~3.0):(0.31~1.86).
[0033] Preferably, the ratio of SiO2 nanospheres to γ-aminopropyltriethoxysilane is (0.5-2.5) g: (100-500) μL; The ratio of SiO2 nanospheres to dispersant water and toluene is (0.5~2.5) g: (50~250) mL: (10~50) mL; The mass ratio of SiO2 nanospheres to hexadecyltrimethylammonium bromide is (0.5~2.5):(0.31~1.55).
[0034] S2: adding acrylic acid, 4-cyano-4-(phenylthioformylthio) valeric acid and azobisisobutyronitrile to tetrahydrofuran for a primary reaction to obtain a first product; adding the first product, perfluorodecyl acrylate and azobisisobutyronitrile to tetrahydrofuran for a secondary reaction to obtain an amphiphilic fluorinated block copolymer PAA-b-PFADE; In a specific process, step S2 is: S21: acrylic acid, 4-cyano-4-(phenylthiocarboxymethylthio) valeric acid, a first volume of azobisisobutyronitrile and a first volume of tetrahydrofuran are mixed, reacted at 75-90° C. for 7-12 hours to obtain a first mixed solution, and vacuum-dried at 25-35° C. for 24-48 hours to obtain a first product. S22: The first product, perfluorodecyl acrylate, a second volume of azobisisobutyronitrile and a second volume of tetrahydrofuran are mixed, reacted at 75-90°C for 7-12 hours to obtain a second mixed solution, and the mixture is distilled under reduced pressure and vacuum dried at 25-35°C for 24-48 hours to obtain an amphiphilic fluorinated block copolymer PAA-b-PFADE.
[0035] The mass ratio of acrylic acid to 4-cyano-4-(phenylthioformylthio)pentanoic acid and perfluorodecyl acrylate is 7:0.2:(15.5~51.8); the length of the lyophobic segment is adjusted by adjusting the mass ratio of the lyophilic and lyophobic monomers acrylic acid to perfluorodecyl acrylate. When the mass is low, the super-amphiphobic performance of the coating is poor. As the length of the lyophobic block increases, the super-amphiphobic performance of the coating increases. When the length of the lyophobic block increases to a certain size, the length continues to increase, the entanglement between molecules becomes larger, and the activity of the carboxyl group is affected. Therefore, the reactivity of the γ-aminopropyltriethoxysilane-modified NH2-SiO2 nanospheres is reduced, resulting in a weakened super-amphiphobic performance.
[0036] Further preferably, the ratio (feed ratio) of acrylic acid, 4-cyano-4-(phenylthioformylthio) valeric acid, the first volume of azobisisobutyronitrile, the first volume of tetrahydrofuran, perfluorodecyl acrylate, the second volume of azobisisobutyronitrile and the second volume of tetrahydrofuran is 7.206 g: 0.19 g: 0.055 g: 70 mL: (15.544-51.817) g: 0.016 g: 70 mL; S3: The amphiphilic fluorinated block copolymer PAA-b-PFADE, the catalyst and ethanol are mixed, and after ultrasonic dispersion, the system is treated at 40°C for 0.5-3h to activate the carboxyl groups on the amphiphilic fluorinated block copolymer PAA-b-PFADE, and then the γ-aminopropyltriethoxysilane-modified SiO2 nanospheres are added and reacted at 50-70°C for 2-10h to obtain the SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres.
[0037] The mass ratio of the amphiphilic fluorinated block copolymer PAA-b-PFADE to the γ-aminopropyltriethoxysilane-modified SiO2 nanospheres is (0.03-0.18):(0.075-0.45).
[0038] The catalyst is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide; Further preferably, the mass ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide, amphiphilic fluorinated block copolymer PAA-b-PFADE and γ-aminopropyltriethoxysilane modified SiO2 nanospheres is (0.01~0.06):(0.005~0.030):(0.03~0.18):(0.075~0.45).
[0039] The feed ratio of amphiphilic fluorinated block copolymer PAA-b-PFADE and ethanol is (0.03~0.18) g:180 mL.
[0040] The invention also discloses a SiO2 / PAA-b-PFADE amphiphilic Janus nanosphere prepared by the above method. A portion of the surface of the SiO2 nanosphere is modified with hydrophilic amino groups for grafting the amphiphilic block copolymer PAA-b-PFADE.
[0041] The present invention discloses a method for preparing SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres, the preparation method comprising: (1) preparing an amphiphilic fluorinated block copolymer PAA-b-PFADE with excellent performance based on RAFT reaction. (2) using silica monomer as a carrier and a silane coupling agent as a modifier to obtain silica nanospheres with partially modified surfaces after modification. (3) using the modified silica nanospheres as a carrier, modifying the amphiphilic fluorinated block copolymer PAA-b-PFADE to obtain amphiphilic silica Janus nanospheres. The Janus particles have excellent performance and strong applicability, and have great application value in enhancing the liquid-repelling performance and liquid-repelling types of super-amphiphobic particles.
[0042] Also disclosed is the use of the above-mentioned SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres in the preparation of a super-amphiphobic coating. First, a hydroxyl acrylic resin prepolymer solution is coated on the surface of the substrate, and then a mixed solution of a cross-linking agent and the SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres is coated, and the super-amphiphobic coating is obtained after drying.
[0043] In a preferred embodiment, the coating amount of the hydroxylated acrylic resin prepolymer solution, the crosslinking agent and the SiO2 / PAA-b-PFADE amphiphilic Janus nanosphere mixed solution is 0.05-0.06 mL / cm 2 The concentration of the hydroxy acrylic resin prepolymer solution is 0.1-0.6 g / mL, and the concentration of SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres in the mixed solution of the crosslinking agent and SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres is 0.01-0.035 g / mL.
[0044] Here, the solvent used to dissolve the hydroxy acrylic resin prepolymer is ethyl acetate, and the solvent used to disperse the crosslinking agent and the SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres is ethyl acetate.
[0045] In addition, the invention also discloses a super amphiphobic coating prepared by the method.
[0046] The invention discloses a SiO2 / PAA-b-PFADE amphiphilic Janus nanosphere, wherein a portion of the surface of the SiO2 nanosphere retains the original hydroxyl group, and the other portion is grafted with a hydrophilic amino group, and an amphiphilic fluorinated block copolymer is further grafted thereto to provide a superphobic segment, thereby preparing an amphiphilic coating.
[0047] The invention discloses a method for preparing SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres. In the presence of 4-cyano-4-(phenylthioformylthio)pentanoic acid, acrylic acid and perfluorodecyl acrylate are respectively used as hydrophilic and hydrophobic monomers to prepare an amphiphilic fluorinated block copolymer by RAFT polymerization. After reduced pressure distillation, purification and drying, the amphiphilic fluorinated block copolymer PAA-b-PFADE is obtained. The SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres are obtained by acylation reaction of the reactive group carboxyl of the hydrophilic chain segment and the reactive group amino group at one end of the NH2-SiO2 nanosphere modified by gamma-aminopropyltriethoxysilane in an ethanol solution.
[0048] The present invention utilizes SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres to make them directional on the coating surface, with the inorganic end facing the hydroxyl acrylate coating on the coating surface, and the organic lyophobic segment facing the air, and the micro-nano rough structure constructed by the SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres and the low surface energy material provided by the organic lyophobic segment are used to realize the super-amphiphobic performance of the coating, and in addition, the reactive group hydroxyl group of the inorganic end and the isocyanate group on the molecular chain of the hydroxyl acrylate crosslinking agent hexamethylene diisocyanate produce chemical crosslinking to improve the wear resistance of the coating. The super-amphiphobic coating prepared by the SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres of the present invention has an oil contact angle of 150°~153°, an oil rolling angle of 4°~8°, a water contact angle of 150°~153°, and a water rolling angle of 4°~8°.
[0049] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0050] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0051] Example 1 A method for preparing SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres, comprising the following steps Step 1, 0.50g SiO2 nanospheres with a particle size of 30nm, 0.31g hexadecyltrimethylammonium bromide, 50mL deionized water, and 10mL toluene are mixed and ultrasonically dispersed, the temperature is raised to 20°C, and the treatment is carried out for 20min. Then, 1.5mL deionized water and 1.5mL ammonia water are added and the temperature is raised to 85°C, and the temperature is kept for 1h. Then, 100μL γ-aminopropyltriethoxysilane is added, and the temperature is kept at 85°C for 1h. The reaction is then washed with toluene, ethanol, and deionized water in turn, and dried to obtain γ-aminopropyltriethoxysilane-modified NH2-SiO2 nanospheres.
[0052] Step 2, 7.206g of acrylic acid, 0.19g of 4-cyano-4-(phenylthioformylthio) pentanoic acid, 0.055g of azobisisobutyronitrile and 70mL of tetrahydrofuran were mixed, the temperature was raised to 75°C, and the mixture was stirred for 7h, and then the mixture was subjected to reduced pressure distillation and purification. The purified product was placed in a vacuum oven at a temperature of 25°C and dried for 24h to obtain a first product. The first product was mixed with 15.544g of perfluorodecyl acrylate, 0.016g of azobisisobutyronitrile and 70mL of tetrahydrofuran, the temperature was raised to 75°C, and the mixture was stirred for reaction for 7h, and then the mixture was subjected to reduced pressure distillation and purification. The purified product was placed in a vacuum oven at a temperature of 25°C and dried for 24h to obtain an amphiphilic fluorinated block copolymer PAA-b-PFADE.
[0053] Step 3, 0.03g of amphiphilic fluorinated block copolymer PAA-b-PFADE, 0.01g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 0.005g of N-hydroxysuccinimide are mixed with ethanol, ultrasonically dispersed and heated to 40°C for activation for 0.5h, and finally 0.075g of γ-aminopropyltriethoxysilane-modified SiO2 nanospheres are added thereto, the temperature is raised to 50°C for reaction for 2h, and then centrifuged and washed, and dried to obtain SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres.
[0054] Preparation of super-amphiphobic coating based on the above-mentioned SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres: Spray 0.1 g / mL ethyl acetate solution of hydroxy acrylate prepolymer on the substrate surface at a spraying volume of 0.05 mL / cm 2 Then, a solution of SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres and hexamethylene diisocyanate in ethyl acetate with a concentration of 0.01 g / mL was sprayed thereon at a spraying volume of 0.05 mL / cm 2 , and dried to obtain a super-amphiphobic coating.
[0055] Example 2 A method for preparing SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres, comprising the following steps Step 1, 3.00g SiO2 nanospheres with a particle size of 500nm, 1.86g hexadecyltrimethylammonium bromide, 300mL deionized water, and 60mL toluene are mixed and ultrasonically dispersed, heated to 40°C, treated for 40min, then 9mL deionized water and 9mL ammonia water are added and heated to 95°C, and the temperature is kept for 6h, and then 600μL γ-aminopropyltriethoxysilane is added, and the temperature is kept at 95°C for 6h, and the mixture is washed with toluene, ethanol, and deionized water in turn, and dried to obtain γ-aminopropyltriethoxysilane-modified NH2-SiO2 nanospheres.
[0056] Step 2, 7.206g acrylic acid, 0.19g 4-cyano-4-(phenylthioformylthio) pentanoic acid, 0.055g azobisisobutyronitrile and 70mL tetrahydrofuran were mixed, the temperature was raised to 90°C, stirred for 12h, and then subjected to reduced pressure distillation and purification. The purified product was placed in a vacuum oven at a temperature of 35°C and dried for 48h to obtain a first product. The first product was mixed with 51.817g perfluorodecyl acrylate, 0.016g azobisisobutyronitrile and 70mL tetrahydrofuran, the temperature was raised to 90°C, stirred for reaction for 12h, and then subjected to reduced pressure distillation and purification. The purified product was placed in a vacuum oven at a temperature of 35°C and dried for 48h to obtain an amphiphilic fluorinated block copolymer PAA-b-PFADE.
[0057] Step 3, 0.18g of amphiphilic fluorinated block copolymer PAA-b-PFADE, 0.06g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 0.030g of N-hydroxysuccinimide are mixed with ethanol, ultrasonically dispersed, heated to 40°C, activated for 3h, and finally 0.45g of γ-aminopropyltriethoxysilane-modified SiO2 nanospheres are added thereto. The temperature is raised to 70°C, reacted for 10h, centrifuged, washed, and dried to obtain SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres.
[0058] Preparation of super-amphiphobic coating based on the above-mentioned SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres: Spray 0.6 g / mL ethyl acetate solution of hydroxy acrylate prepolymer on the substrate surface at a spraying volume of 0.06 mL / cm 2 Then, a solution of SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres and hexamethylene diisocyanate in ethyl acetate with a concentration of 0.035 g / mL was sprayed thereon at a spraying volume of 0.06 mL / cm 2 , and dried to obtain a super-amphiphobic coating.
[0059] Example 3 A method for preparing SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres, comprising the following steps Step 1, 1g SiO2 nanospheres with a particle size of 150nm, 0.62g hexadecyltrimethylammonium bromide, 100mL deionized water, and 20mL toluene are mixed and ultrasonically dispersed, heated to 25°C, treated for 25min, then 3mL deionized water and 3mL ammonia water are added and heated to 88°C, kept warm for 2h, then 200μL γ-aminopropyltriethoxysilane is added, and the reaction is kept warm at 88°C for 2h, and then washed with toluene, ethanol, and deionized water in turn, and dried to obtain γ-aminopropyltriethoxysilane-modified NH2-SiO2 nanospheres.
[0060] Step 2, 7.206g acrylic acid, 0.19g 4-cyano-4-(phenylthioformylthio) pentanoic acid, 0.055g azobisisobutyronitrile and 70mL tetrahydrofuran were mixed, the temperature was raised to 80°C, stirred for 8h, and then subjected to reduced pressure distillation and purification. The purified product was placed in a vacuum oven at a temperature of 28°C and dried for 30h to obtain a first product. The first product was mixed with 20.725g perfluorodecyl acrylate, 0.016g azobisisobutyronitrile and 70mL tetrahydrofuran, the temperature was raised to 80°C, stirred for reaction for 8h, and then subjected to reduced pressure distillation and purification. The purified product was placed in a vacuum oven at a temperature of 28°C and dried for 30h to obtain an amphiphilic fluorinated block copolymer PAA-b-PFADE.
[0061] Step 3, 0.06g of amphiphilic fluorinated block copolymer PAA-b-PFADE, 0.02g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 0.01g of N-hydroxysuccinimide are mixed with ethanol, ultrasonically dispersed and heated to 40°C for activation for 1h, and finally 0.150g of γ-aminopropyltriethoxysilane-modified SiO2 nanospheres are added thereto, the temperature is raised to 55°C, the reaction is carried out for 4h, and then centrifuged, washed, and dried to obtain SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres.
[0062] Preparation of super-amphiphobic coating based on the above-mentioned SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres: Spray 0.2 g / mL ethyl acetate solution of hydroxy acrylate prepolymer on the substrate surface at a spraying volume of 0.05 mL / cm 2 Then, a solution of SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres and hexamethylene diisocyanate in ethyl acetate with a concentration of 0.015 g / mL was sprayed thereon at a spraying volume of 0.06 mL / cm 2 , and dried to obtain a super-amphiphobic coating.
[0063] Example 4 A method for preparing SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres, comprising the following steps Step 1, 1.5g SiO2 nanospheres with a particle size of 250nm, 0.93g hexadecyltrimethylammonium bromide, 150mL deionized water, and 30mL toluene are mixed and ultrasonically dispersed, the temperature is raised to 30°C, and the treatment is carried out for 30min. Then, 4.5mL deionized water and 4.5mL ammonia water are added and the temperature is raised to 90°C, and the temperature is kept for 3h. Then, 300μL γ-aminopropyltriethoxysilane is added, and the temperature is kept at 90°C for 3h. The reaction is then washed with toluene, ethanol, and deionized water in turn, and dried to obtain γ-aminopropyltriethoxysilane-modified NH2-SiO2 nanospheres.
[0064] Step 2, 7.206g acrylic acid, 0.19g 4-cyano-4-(phenylthioformylthio) pentanoic acid, 0.055g azobisisobutyronitrile and 70mL tetrahydrofuran were mixed, the temperature was raised to 83°C, stirred for 9h, and then subjected to reduced pressure distillation and purification. The purified product was placed in a vacuum oven at a temperature of 30°C and dried for 36h to obtain the first product. The first product was mixed with 25.907g perfluorodecyl acrylate, 0.016g azobisisobutyronitrile and 70mL tetrahydrofuran, the temperature was raised to 83°C, stirred for reaction for 9h, and then subjected to reduced pressure distillation and purification. The purified product was placed in a vacuum oven at a temperature of 30°C and dried for 36h to obtain an amphiphilic fluorinated block copolymer PAA-b-PFADE.
[0065] Step 3, 0.09g of amphiphilic fluorinated block copolymer PAA-b-PFADE, 0.03g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 0.015g of N-hydroxysuccinimide are mixed with ethanol, ultrasonically dispersed and heated to 40°C for activation for 1.5h, and finally 0.225g of γ-aminopropyltriethoxysilane-modified SiO2Janus nanospheres are added thereto, the temperature is raised to 60°C, the reaction is carried out for 6h, and then centrifuged, washed, and dried to obtain SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres.
[0066] Preparation of super-amphiphobic coating based on the above-mentioned SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres: Spray 0.5 g / mL ethyl acetate solution of hydroxy acrylate prepolymer on the substrate surface at a spraying volume of 0.06 mL / cm 2 Then, SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres and ethyl acetate solution of hexamethylene diisocyanate with a concentration of 0.030 g / mL were sprayed thereon, and the spraying amount was 0.05 mL / cm 2 , and dried to obtain a super-amphiphobic coating.
[0067] Example 5 A method for preparing SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres, comprising the following steps Step 1, 2.00g SiO2 nanospheres with a particle size of 350nm, 1.24g hexadecyltrimethylammonium bromide, 200mL deionized water, and 40mL toluene are mixed and ultrasonically dispersed, the temperature is raised to 33°C, and the temperature is kept for 33min, and then 6mL deionized water and 6mL ammonia water are added and the temperature is raised to 92°C, and the temperature is kept for 4h, and then 400μL γ-aminopropyltriethoxysilane is added, and the temperature is kept at 92°C for 4h, and the reaction is kept for 4h, and the reaction is washed with toluene, ethanol, and deionized water in turn, and dried to obtain γ-aminopropyltriethoxysilane-modified NH2-SiO2 nanospheres.
[0068] Step 2, 7.206g acrylic acid, 0.19g 4-cyano-4-(phenylthioformylthio) pentanoic acid, 0.055g azobisisobutyronitrile and 70mL tetrahydrofuran were mixed, the temperature was raised to 85°C, stirred for 10h, and then subjected to reduced pressure distillation and purification. The purified product was placed in a vacuum oven at a temperature of 32°C and dried for 42h to obtain a first product. The first product was mixed with 25.907g perfluorodecyl acrylate, 0.016g azobisisobutyronitrile and 70mL tetrahydrofuran, the temperature was raised to 88°C, stirred for reaction for 10h, and then subjected to reduced pressure distillation and purification. The purified product was placed in a vacuum oven at a temperature of 32°C and dried for 42h to obtain an amphiphilic fluorinated block copolymer PAA-b-PFADE.
[0069] Step 3, 0.12g of amphiphilic fluorinated block copolymer PAA-b-PFADE, 0.040g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 0.020g of N-hydroxysuccinimide are mixed with ethanol, ultrasonically dispersed and heated to 40°C for activation for 2h, and finally 0.30g of γ-aminopropyltriethoxysilane-modified SiO2 nanospheres are added thereto, the temperature is raised to 65°C, the reaction is performed for 6h, and then centrifuged, washed, and dried to obtain SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres.
[0070] Preparation of super-amphiphobic coating based on the above-mentioned SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres: Spray 0.4 g / mL ethyl acetate solution of hydroxy acrylate prepolymer on the substrate surface at a spraying volume of 0.055 mL / cm 2 Then, a solution of SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres and hexamethylene diisocyanate in ethyl acetate with a concentration of 0.025 g / mL was sprayed thereon, and the spraying amount was 0.055 mL / cm 2 , and dried to obtain a super-amphiphobic coating.
[0071] Taking Example 2 as an example, the NH2-SiO2Janus nanospheres prepared in Example 2 were used for silver labeling. The NH2-SiO2Janus nanospheres were dispersed in a silver nitrate solution, and the silver ions were reduced after adding water and hydrazine. The microscopic morphology of the labeled NH2-SiO2Janus nanospheres was characterized, and the TEM results were as follows: Figure 1 As shown. Figure 1 It can be seen that the NH2-SiO2Janus nanospheres contain silver particles only at one end and have a significant asymmetric structure, indicating that the NH2-SiO2Janus nanospheres were successfully prepared using this method.
[0072] Figure 2The SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres were formed by grafting the amphiphilic fluorinated block copolymer PAA-b-PFADE onto NH2-SiO2Janus nanospheres. The microstructure of the nanospheres was characterized. The TEM results are shown in Figure 2. Figure 2 As shown. Figure 2 It can be seen that only a part of the surface of the SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres contains the amphiphilic fluorinated block copolymer PAA-b-PFADE, which has a significant asymmetric structure, indicating that the SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres were successfully prepared by this method.
[0073] Figure 3 This is an optical microscope photo of the SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres stabilized emulsion. The SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres were added to a mixed emulsion of dodecane and dimethyl sulfoxide, and ultrasonic cell crushing and emulsification were performed for ten minutes. The emulsion was placed under an upright microscope, and its stable emulsion droplets could be observed, indicating that it has amphiphilicity.
[0074] Figure 4 The contact angle test results of different liquids on the super-amphiphobic coating prepared in Example 2 of the present invention after thirty friction tests; Figure 4 It can be seen that the super-amphiphobic coating prepared by the present invention still has good super-amphiphobic performance after several friction tests, wherein the water contact angle is 152°±0.9°, and the oil contact angle is 151±0.4°, and has excellent liquid-repellent performance.
[0075] Figure 5 The water contact angle and rolling contact angle test results of the super double-repellent coating constructed based on SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres after different cyclic friction experiments are shown in the figure. As shown in the figure, when not rubbed, the super double-repellent coating shows excellent super-hydrophobic performance, and its water contact angle and rolling angle are 159.7 ± 1.1 ° and 1.9 ± 0.3 ° respectively. With the increase of the number of frictions, the water contact angle of the coating gradually decreases, and the rolling angle gradually increases. After 50 friction cycles, the water contact angle and rolling angle of the coating are 152.2 ± 3.2 ° and 8.9 ± 0.2 ° respectively, indicating that the coating still has significant super-hydrophobic ability. The superiority of this wear resistance is due to the chemical crosslinking and physical bonding between SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres and hydroxy acrylic resin, which effectively suppresses the shedding of nanospheres during friction, thereby ensuring the micro-nanostructure stability of the coating surface, and significantly improving its wear-resistant super-hydrophobic performance.
[0076] Figure 6The hexadecane contact angle and rolling contact angle test results of the super-amphiphobic coating constructed based on SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres prepared in Example 2 of the present invention after different cyclic friction experiments, as shown in the figure, when not rubbed, the super-amphiphobic coating exhibits excellent super-oleophobic performance, and its hexadecane contact angle and rolling angle are 157.8 ± 0.9 ° and 2.6 ± 0.7 ° respectively. With the increase of the number of frictions, the oil contact angle of the coating gradually decreases, and the rolling angle gradually increases. After 50 friction cycles, the oil contact angle and rolling angle are 150.3 ± 0.7 ° and 9.4 ± 0.5 ° respectively, indicating that the coating still has super-oleophobic ability. This excellent wear resistance is attributed to the chemical crosslinking reaction and physical bonding force between SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres and hydroxy acrylic resin, which effectively hinders the shedding of nanospheres during friction, thereby maintaining the super-oleophobic properties and stability of the coating.
[0077] The above friction experiment is specifically as follows: In order to evaluate the wear resistance of the super-amphiphobic coating constructed by SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres, a hydroxy acrylic resin was used as a primer, and the coating was prepared on a glass slide by spraying, and the sandpaper friction experiment was used for testing. The specific method is: the coating sample is placed on 400-mesh sandpaper, a 50g weight is loaded on the glass slide, and a friction cycle of 10 cm in the horizontal and vertical directions is taken as one friction cycle. The glass slide is moved at a constant speed, and the changes in the water contact angle, oil contact angle and rolling angle of the coating after the friction cycle are recorded to evaluate the super-amphiphobic performance and wear resistance stability of the coating under friction.
[0078] In summary, the present invention successfully prepared NH2-SiO2Janus nanospheres by an emulsion interface method, and then successfully prepared SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres by an acylation reaction with an amphiphilic fluorinated block copolymer, and then by layer-by-layer spraying, the hydrophilic end was chemically cross-linked with the substrate to obtain a super amphiphobic coating.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres, characterized in that: The following steps are involved: SiO2 nanospheres and hexadecyltrimethylammonium bromide are added into a two-phase solvent of water and toluene, and then the pH value of the system is adjusted to 7-8, and γ-aminopropyltriethoxysilane is added for reaction to obtain γ-aminopropyltriethoxysilane-modified SiO2 nanospheres; Acrylic acid, 4-cyano-4-(phenylthioformylthio) valeric acid and azobisisobutyronitrile are added to tetrahydrofuran for a primary reaction to obtain a first product; the first product, perfluorodecyl acrylate and azobisisobutyronitrile are added to tetrahydrofuran for a secondary reaction to obtain an amphiphilic fluorinated block copolymer PAA-b-PFADE; The amphiphilic fluorinated block copolymer PAA-b-PFADE, a catalyst and ethanol are mixed, ultrasonically dispersed, and the γ-aminopropyltriethoxysilane-modified SiO2 nanospheres are added. After reaction, the SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres are obtained.
2. The method for preparing SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres according to claim 1, characterized in that: The particle size of the SiO2 nanospheres is 30-500 nm.
3. The method for preparing SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres according to claim 1, characterized in that: The ratio of the SiO2 nanospheres to γ-aminopropyltriethoxysilane is (0.5-3.0) g: (100-600) μL.
4. The method for preparing SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres according to claim 1, characterized in that: The mass ratio of the acrylic acid to 4-cyano-4-(phenylthioformylthio)pentanoic acid and perfluorodecyl acrylate is 7:0.2:(15.5-51.8).
5. The method for preparing SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres according to claim 1, characterized in that: During the primary reaction, the reaction temperature is 75-90° C. and the reaction time is 7-12 h; during the secondary reaction, the reaction temperature is 75-90° C. and the reaction time is 7-12 h.
6. The method for preparing SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres according to claim 1, characterized in that: The mass ratio of the amphiphilic fluorinated block copolymer PAA-b-PFADE to the γ-aminopropyltriethoxysilane-modified SiO2 nanospheres is (0.03-0.18):(0.075-0.45).
7. A SiO2 / PAA-b-PFADE amphiphilic Janus nanosphere, characterized in that: Prepared by the method according to any one of claims 1 to 6.
8. The use of SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres as claimed in claim 7 in the preparation of super-amphiphobic coatings, characterized in that: First, a hydroxy acrylic resin prepolymer solution is coated on the surface of the substrate, and then a mixed solution of a crosslinking agent and the SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres is coated, and a super amphiphobic coating is obtained after drying.
9. The use of SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres in the preparation of super-amphiphobic coatings according to claim 8, characterized in that: The coating amount of the hydroxy acrylic resin prepolymer solution, the crosslinking agent and the SiO2 / PAA-b-PFADE amphiphilic Janus nanosphere mixed solution is 0.05-0.06 mL / cm 2 The concentration of the hydroxy acrylic resin prepolymer solution is 0.1-0.6 g / mL, and the concentration of SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres in the mixed solution of the crosslinking agent and SiO2 / PAA-b-PFADE amphiphilic Janus nanospheres is 0.01-0.035 g / mL.
10. A super amphiphobic coating, characterized in that: Prepared by the method described in any one of claims 8 to 9; the super amphiphobic coating has an oil contact angle of 150° to 157°, an oil rolling angle of 2.6° to 9.4°, a water contact angle of 152° to 160°, and a water rolling angle of 1.9° to 9°.
Citation Information
Patent Citations
Fluorine-containing polyacrylate coating agent based on amphiphilic Janus SiO2 nanoparticles and preparation method thereof
CN111995708A
SiO2 / PAA-b-PS amphiphilic Janus microsphere, preparation method and application thereof
CN113980211A
Cited By
Wet-end papermaking process for improving surface smoothness of paper
CN120193440A